Internet use during childhood and the ecological techno-subsystem - Genevieve Marie Johnson; Korbla P. Puplampu (The Canadian Network for Innovation in Education (CNIE), 2008)
Research findings suggest both positive and negative developmental consequences of Internet use during childhood (e.g., playing video games have been associated with enhanced visual skills as well as increased aggression). Several studies have concluded that environmental factors mediate the developmental impact of childhood online behaviour. From an ecological perspective, we propose the techno-subsystem, a dimension of the microsystem (i.e., immediate environments). The techno-subsystem includes child interaction with both living (e.g., peers) and nonliving (e.g., hardware) elements of communication, information, and recreation technologies in direct environments. By emphasizing the role of technology in child development, the ecological techno-subsystem encourages holistic exploration of the developmental consequences of Internet use (and future technological advances) during childhood. L'usage d'Internet chez les enfants et le sous-système Techno écologique Résumé : Les résultats de recherche semblent indiquer que l'usage d'Internet chez les enfants aurait des conséquences développementales qui soit à la fois positives et négatives (ex. : l'usage des jeux vidéo auraient été associés à un accroissement des habileté visuelles ainsi qu'à un accroissement de l'agressivité). Plusieurs études ont aussi conclue que l'impact du comportement des enfants quand il sont en ligne sur leur développement serait affecté par des facteurs environnementaux. Dans une perspective écologique, nous proposons le sous-système Techno, une dimension du microsystème (ex :. les environnements immédiats). Le sous-système Techno comprend l'interaction de l'enfant avec des éléments vivants (e. : les paires) et non vivants (ex; les ordinateurs) de communication, d'information et de technologie de jeux dans des environnements directes.